Studi Diskriptif Pengguna Metode Kontrasepsi Modern - Wiwin Hindriyawati; Tatik; Reni Tri Lestari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Family planning program is also specifically designed to create progress, stability, andeconomic, social, and spiritual prosperity for every resident. The family planning program inIndonesia is regulated in Law No. 10 of 1992. The prevalence of contraceptive use amongwomen aged 15-49 years with marital status is 59.3% using modern methods (Implant, MOW,MOP, IUD, Condoms, Pills), 0.4 % used traditional contraception (MAL/Breastfeeding,Periodic/calendar abstinence, interrupted intercourse, others), 24.7% had ever done familyplanning, and 15.5% had never done family planning. Method research uses Descriptiveobservational method using cross sectional design, sampling with total sampling technique. Thesample of this research is couples of childbearing age who use modern contraception as manyas 249 respondents, by collecting secondary data. The results of the descriptive statistical testshowed that most of the respondents were aged > 35 years, 152 (61.0%), the largestrespondent's education was high school education 102 (42%), the largest respondent'soccupation was as a casual worker as many as 80 (12.0%), the largest parity was in the numberof living children 2 were 126 (50.6%), the most used contraceptive method was the Non-MKJPmethod 193 (77.5%), with the largest injection contraception 160 (64.3%). In conclusion, mostof the respondents are >35 years old, with high school education, type of casual work, mostparity has 2 living children, non-MKJP contraceptive users with injection dominantcontraception.Keywords: Age, Education, Occupation, Parity, Modern Contraceptive Methods